SECURING QR CODES WITH ENCRYPTION SCHEMES: A SURVEY - TARUNIKA,; SAHOO, ANITA (International Journal of Computer Sciences and Engineering, 2025)
QR code (shortened from Quick Response code) matrix barcode (or two-dimensional code) initially intended for the car business is a trademark. QR code on the Internet, with the quick advancement of the transmission required, for the security of computerized data against unlawful use turns out to be increasingly imperative. To overcome basic restrictions in the one-dimensional disorganized framework,, our proposed scheme presents good encryption system with large key space. Due to bulky data capacity and very high relationship among pixels in QR Code documents, customary methods are not appropriate for QR Code encryption. QR code to get this paper proposes a chaotic scheme, enormous information limit and high relationship between's pixels in QR codes as documents, conventional systems are not reasonable for encryption QR code. (For example, AES and DES) as contrasted and chaos-based encryption schemes QR code has done well.